2015
DOI: 10.1038/nrneurol.2015.226
|View full text |Cite
|
Sign up to set email alerts
|

Genetic risk factors for spontaneous intracerebral haemorrhage

Abstract: Intracerebral haemorrhage (ICH) is associated with the greatest morbidity and mortality of all stroke subtypes. Established risk factors for ICH include hypertension, alcohol use, current cigarette smoking, and use of oral anticoagulants and/or antiplatelet agents. Familial aggregation of ICH has been observed, and the heritability of ICH risk has been estimated at 44%. Few genes have been found to be associated with ICH at the population level, and much of the evidence for genetic risk factors for ICH comes f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
50
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 120 publications
3
50
0
3
Order By: Relevance
“…25 Promising candidates for risk alleles in ICH identified in populations (which had no continental Africans), include variants of the genes Apolipoprotein E ( APOE ), ACE, PMF1/SLC25A44 , COL4A2 , and MTHFR 18, 23, 26 . Other genetic variants related to hemostasis, lipid metabolism, inflammation, and the central nervous system microenvironment as well as the locus 1q22 25 have also been linked to ICH in single candidate gene studies.…”
Section: 0 Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Promising candidates for risk alleles in ICH identified in populations (which had no continental Africans), include variants of the genes Apolipoprotein E ( APOE ), ACE, PMF1/SLC25A44 , COL4A2 , and MTHFR 18, 23, 26 . Other genetic variants related to hemostasis, lipid metabolism, inflammation, and the central nervous system microenvironment as well as the locus 1q22 25 have also been linked to ICH in single candidate gene studies.…”
Section: 0 Discussionmentioning
confidence: 99%
“…Other genetic variants related to hemostasis, lipid metabolism, inflammation, and the central nervous system microenvironment as well as the locus 1q22 25 have also been linked to ICH in single candidate gene studies. 26 …”
Section: 0 Discussionmentioning
confidence: 99%
“…Although life-style factors such as tobacco/alcohol consumption, hypertension, trauma, anti-coagulant, and anti-platelet therapies have been implicated in ICH pathobiology, relatively little is known about the extent to which familial and hereditary factors contribute to spontaneous ICH in humans. In a recent review of the known human genetic risk factors for ICH, Carpenter et al, have shown, based on previous meta analyses and genet-association studies, several genes to be implicated in ICH pathobiology (Carpenter et al, 2015). They suggest that mutations in genes regulating the processes of hemostasis, lipid metabolism and transfer, as well as inflammation (APOE, ACE, PMF1/SLC25A44, COL4A2, and MTHFR) can predispose individuals to spontaneous ICH (Carpenter et al, 2015).…”
Section: Conclusion/discussionmentioning
confidence: 99%
“…In a recent review of the known human genetic risk factors for ICH, Carpenter et al, have shown, based on previous meta analyses and genet-association studies, several genes to be implicated in ICH pathobiology (Carpenter et al, 2015). They suggest that mutations in genes regulating the processes of hemostasis, lipid metabolism and transfer, as well as inflammation (APOE, ACE, PMF1/SLC25A44, COL4A2, and MTHFR) can predispose individuals to spontaneous ICH (Carpenter et al, 2015). Although such gene-association studies do not yield mechanistic insights into how deficiencies in these gene products may contribute to the etiology of spontaneous ICH, they do offer candidate pathways as points of therapeutic intervention to prevent vascular leakage.…”
Section: Conclusion/discussionmentioning
confidence: 99%
“…Instead of looking at these patients as individuals with SCD who typically happen to be black, we believe a better approach is to view them as individuals with predominantly African genetic heritage who also happen to have SCD, which can be seen as a significant stressor in the presence of which otherwise minor variants with little health impact in isolation become important determinants of health. We discuss exemplary domains in which genomic studies have yielded promising results in populations without SCD including (1) APOE, specifically the prevalence of the APOE‐ε4 ; (2) genes identified from African or African American studies predisposing to hypertension; (3) APOL1 G1/G2 variants; (4) haptoglobin haplotype (H2/2 allelic pattern); and (5) other genes associated with intracerebral hemorrhage including ACE, PMF1/SLC25A44, COL4A2, and MTHFR …”
mentioning
confidence: 99%